Languages and technologies in education at school and outside of school: Perspectives from young people in low-resource countries in Africa and Asia - Kukulska-Hulme, Agnes; Giri, Ram Ashish; Dawadi, Saraswati; Devkota, Kamal Raj; Gaved, Mark (Frontiers in Communication, 2023)
Disadvantaged children in low-resource countries are less likely to complete their education or to progress to higher levels, which means that their upward mobility can be severely constrained. Versatile technologies such as smartphones, when combined with an ability to use the English language, can facilitate access to learning resources, thereby helping to support young people’s education where the school facilities and local teaching resources are often insufficient and may reinforce existing inequalities. However, technology access and usage vary, and linguistic or other barriers to effective engagement are multifaceted. To gain a deeper understanding of the role of languages and technologies, our research project collected first-hand accounts of the educational experiences of marginalised young people aged 13-15, their parents and teachers in harder-to-reach urban and rural settings, in four low-income countries in Africa and Asia. The research investigated perspectives on the English language and use of technology in education in school and outside of school. Our findings provide unique insights into local cultures of technology use and English language use in the context of children’s lived experiences. The paper covers students’ use of English and attitudes towards English alongside other languages in their local setting, and how they are learning with mobile digital devices at school, at home, outdoors, and in the homes of relatives, friends and neighbours. Relationships between languages and technologies are discussed, as well as the sustainability of English- and technology-mediated education in the countries in question, which will have broader applicability in other low-resource settings.